2007
DOI: 10.1161/circulationaha.106.658807
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Functional Atrioventricular Accessory Pathways in Postseptated Embryonic Avian Hearts

Abstract: Background-During heart development, the ventricular activation sequence changes from a base-to-apex to an apex-to-base pattern. We investigated the possibility of impulse propagation through remnants of atrioventricular (AV) connections in quail hearts. Methods and Results-In 86 hearts (group A, nϭ15; group B, nϭ65; group C, 5 to 6 months, nϭ6) electrodes were positioned at the left atrium, right ventricular base, left ventricular (LV) base, and LV apex. In group A, LV base activation preceded LV apex activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
6
26
0
Order By: Relevance
“…Recently, similar APs were demonstrated during normal quail heart development, where most APs were found at the posteroseptal aspect of the tricuspid valve orifice (12). In contrast, we demonstrated the majority of APs at the anterolateral aspect of mitral orifice in mouse.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Recently, similar APs were demonstrated during normal quail heart development, where most APs were found at the posteroseptal aspect of the tricuspid valve orifice (12). In contrast, we demonstrated the majority of APs at the anterolateral aspect of mitral orifice in mouse.…”
Section: Discussionsupporting
confidence: 82%
“…It has been suggested that APs involved in these tachycardias are remnants of the primary AV canal myocardium, which disappear during development and maturation of the annulus fibrosus before and after birth (12,18). Although presence of APs has been demonstrated during normal cardiac development in human fetuses and neonates, their etiology and conducting properties as well as their causative role in AVRT are largely unrevealed (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirectly, the abnormal formation of the fibrous annulus with persisting accessory pathways can result in reentry tachycardias. PEO inhibition in chick embryos showed defective atrioventricular isolation, delaying the shift from a base-to-apex to an apex-to-base conduction [17].…”
Section: Conduction System Anomaliesmentioning
confidence: 95%